NMR spectroscopic search module for Spektraris, an online resource for plant natural product identification – Taxane diterpenoids from Taxus × media cell suspension cultures as a case study. (May 2015) - Fischedick, Justin T.; Johnson, Sean R.; Ketchum, Raymond E.B.; Croteau, Rodney B.; Lange, B. Markus
Graphical abstract: Development and testing of Spektraris-NMR – a resource for identifying known plant natural products based on NMR spectra. Highlights: Introduction of Spektraris-NMR resource for identification of known plant natural products. Utility demonstrated by successful identification of taxanes isolated from Taxus cell cultures. Structure of a novel taxane, 2-deacetylbaccatin IV, is also determined. Spektraris NMR is a valuable tool for dereplication efforts in natural products isolation. Abstract: Development and testing of Spektraris-NMR, an online spectral resource, is reported for the NMR-based structural identification of plant natural products (PNPs). Spektraris-NMR allows users to search with multiple spectra at once and returns a table with a list of hits arranged according to the goodness of fit between query data and database entries. For each hit, a link to a tabulated alignment of 1 H NMR and 13 C NMR spectroscopic peaks (query versus database entry) is provided. Furthermore, full spectroscopic records and experimental meta information about each database entry can be accessed online. To test the utility of Spektraris-NMR for PNP identification, the database was populated with NMR data (total of 466 spectra) for ∼250 taxanes, which are structurally complex diterpenoids (including the anticancer drug taxol) commonly found in the genus Taxus . NMR data generated with metabolites purified from Taxus cell suspension cultures were then used to search Spektraris-NMR, and enabled the identification of eight taxanes with high confidence. A ninth isolated metabolite could be assigned, based on spectral searches, to a taxane skeletal class, but no high confidence hit was produced. Using various spectroscopic methods, this metabolite was characterized as 2-deacetylbaccatin IV, a novel taxane. These results indicate that Spektraris-NMR is a valuable resource for rapid and reliable identification of known metabolites and has the potential to contribute to de-replication efforts in novel PNP discovery.